2018
DOI: 10.31086/tjgeri.2018137964
|View full text |Cite
|
Sign up to set email alerts
|

Can an Elective Geriatric Nursing Course Change Nursing Students' Attitudes and Willingness in Caring for the Elderly? A Quasi-Experimental Design Study

Abstract: Introduction:The elderly population is rapidly growing, and healthcare professionals are currently providing increased care for the elderly. This study was conducted to evaluate the effect of an elective geriatric nursing course on the attitude of students toward the elderly and students' willingness to work with them.Materials and Method: This study was a quasi-experimental. Pretest-posttest design was used. The sample comprised 108 nursing students (46 of the students were educated in an elective geriatric n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…That caring for older adults is one of the least desired career choices among nursing students is a global phenomenon (Dai et al, 2020;Hsieh & Chen, 2019). In Malaysia, knowledge of older adults did not translate to intention (Che et al, 2018), which was also true in Sri Lanka (Rathnayake et al, 2016), Taiwan (Hsieh & Chen, 2019), China (Cheng et al, 2020), Portugal (Paulo de Almeida Tavares et al, 2014) and Turkey (Akpinar Soylemez et al, 2018). Thus, nursing programs must nurture the development of positive attitudes toward older adults and foster an intent to work with this population.…”
Section: Introductionmentioning
confidence: 99%
“…That caring for older adults is one of the least desired career choices among nursing students is a global phenomenon (Dai et al, 2020;Hsieh & Chen, 2019). In Malaysia, knowledge of older adults did not translate to intention (Che et al, 2018), which was also true in Sri Lanka (Rathnayake et al, 2016), Taiwan (Hsieh & Chen, 2019), China (Cheng et al, 2020), Portugal (Paulo de Almeida Tavares et al, 2014) and Turkey (Akpinar Soylemez et al, 2018). Thus, nursing programs must nurture the development of positive attitudes toward older adults and foster an intent to work with this population.…”
Section: Introductionmentioning
confidence: 99%
“…In Akpinar Soylemez et al. ( 2018 ), no statistical differences were found regarding students’ willingness to work with older people before and after the students’ taking an elective geriatric nursing course and an elective emergency and surgery nursing course. Cheng et al.…”
Section: Resultsmentioning
confidence: 93%
“…Concerning educational level, although some researchers have explored various courses and training programmes in recent years, many studies (Akpinar Soylemez et al., 2018 ; Che et al., 2018 ; Cheng et al., 2020 ; Lamet et al., 2011 ) have failed to find significant differences compared with the control groups or show significant improvements in students’ willingness to work with older people, thus indicating that more efficient educational strategies should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the research, it was observed that, before the KOPS pre-test, students provided predominantly positive responses to questions regarding knowledge and attitudes about old age. In studies examining how geriatric nursing course affects the attitude towards the elderly in our country, it has been observed that students mostly give positive answers to similar questions and their attitudes towards the elderly are positive [13][14][15][16] . This situation can be attributed to the cultural characteristics in our country.…”
Section: Discussionmentioning
confidence: 99%